Development of a rapid colorimetric multiplex PCR‐reverse line blot for the detection and typing of 14Chlamydia trachomatisgenovars. Issue 11 (November 2018) - Molano, Monica; Tabrizi, Sepehr N.; Phillips, Samuel; Danielewski, Jennifer; Cornall, Alyssa; Morre, Servaas A.; Garland, Suzanne M.
Abstract : Purpose. : Chlamydiatrachomatis is responsible for trachoma‐associated blindness as well as the most common sexually transmitted bacterial infection worldwide, although the genovars for the former are typically A‐C, whilst for the latter they are D‐K and for the uncommon infection lymphogranuloma venereum they are L1‐3. Nucleotide variations within the ompA gene facilitate the identification of C. trachomatis genovars. This study describes a colorimetric multiplex PCR/RLB typing assay (mPCR‐RLB) directed to the VD2 region of the ompA gene for general C. trachomatis positivity and the identification of 14 individual C. trachomatis genovars. Methodology. : The assay was validated by analysing 40 blinded samples that included reference strains of C. trachomatis genovars and other non‐chlamydial micro‐organisms that had been analysed previously using quantitative PCR (qPCR). Ninety clinical samples that had previously been found to be C. trachomatis ‐positive by qPCR were also evaluated using the mPCR‐RLB assay. Results. : The mPCR‐RLB assay showed 100 % agreement with the qPCR in the detection of C. trachomatis reference strains and no cross‐reaction of non‐chlamydial micro‐organisms was observed. In the analysis of the chlamydial clinical samples, 97.8 % were C. trachomatis ‐positive by mPCR/RLB assay and there was a 96.6 % concordance with the qPCR at the group identification level and a 92.2 % concordance at the genovar level. Conclusion. : The mPCR‐RLB assay is a rapid and sensitive methodology for the identification of C. trachomatis genovars associated with urogenital infections, trachoma or lymphogranuloma venereum diseases that can be implemented in clinical settings, helping to identify reinfections and treatment failures and establish the appropriate treatment course.